Nitrogen in the environment sources, problems, and management - Follett, R. F. (Ronald F.), 1939-; Hatfield, Jerry L. (Amsterdam ; New York : Elsevier Academic Press, 2001)
Nitrogen in the Environment: Sources, Problems, and Management is the first volume to provide a holistic perspective and comprehensive treatment of nitrogen from field, to ecosystem, to treatment of urban and rural drinking water supplies, while also including a historical overview, human health impacts and policy considerations. It provides a worldwide perspective on nitrogen and agriculture. Nitrogen is one of the most critical elements required in agricultural systems for the production of crops for feed, food and fiber. The ever-increasing world population requires increasing use of nitrogen in agriculture to supply human needs for dietary protein. Worldwide demand for nitrogen will increase as a direct response to increasing population. Strategies and perspectives are considered to improve nitrogen-use efficiency. Issues of nitrogen in crop and human nutrition, and transport and transformations along the continuum from farm field to ground water, watersheds, streams, rivers, and coastal marine environments are discussed. Described are aerial transport of nitrogen from livestock and agricultural systems and the potential for deposition and impacts. The current status of nitrogen in the environment in selected terrestrial and coastal environments and crop and forest ecosystems and development of emerging technologies to minimize nitrogen impacts on the environment are addressed. The nitrogen cycle provides a framework for assessing broad scale or even global strategies to improve nitrogen use efficiency. Growing human populations are the driving force that requires increased nitrogen inputs. These increasing inputs into the food-production system directly result in increased livestock and human-excretory nitrogen contribution into the environment. The scope of this book is diverse, covering a range of topics and issues from furthering our understanding of nitrogen in the environment to policy considerations at both farm and national scales.
The nitrogen cycle, historical perspective, and current and potential future concerns / D.R. Keeney and J.L. Hatfield -- Nitrogen transformation and transport processes / Ronald F. Follett -- Importance and effect of nitrogen on crop quality and health / J{uml}urg M. Blumenthal, David D. Baltensperger, Kenneth G. Cassman, Stephen C. Mason and Alexander D. Pavlista -- Utilization and metabolism of nitrogen by humans / Jennifer R. Follett and Ronald F. Follett -- Nitrate losses to surface water through subsurface, tile drainage / G.W. Randall and M.J. Goss -- Nitrogen in groundwater associated with agricultural systems / Michael R. Burkart and Jeffrey D. Stoner -- The importance and role of watersheds in the transport of nitrogen / T.J. Sauer, R.B. Alexander, J.V. Brahana and R.A. Smith -- Nitrogen transport and fate in European streams, rivers, lakes and wetlands / B. Kronvang, J.P. Jensen, C.C. Hoffmann and P. Boers -- Nitrogen effects on coastal marine ecosystems / John R. Kelly -- Gaseous nitrogen emissions from livestock farming systems / Oene Oenema, Andr{acute}e Bannink, Sven G. Sommer and Gerard L. Velthof -- Exchange of gaseous nitrogen compounds between terrestrial systems and the atmosphere / A.R. Mosier -- The impacts of nitrogen deposition on forest ecosystems / K.J. Nadelhoffer -- On-farm technologies and practices to improve nitrogen use efficiency / N.R. Kitchen and K.W.T. Goulding -- Developing software for livestock manure and nutrient management in the USA / Philip J. Hess, Brad C. Joern and John A. Lory -- Field techniques for modeling nitrogen management / Marvin J. Shaffer and Jorge A. Delgado -- Simulated effects of land use, soil texture, and precipitation on N gas emissions using DAYCENT / S.J. Del Grosso, W.J. Parton, A.R. Mosier, M.D. Hartman, C.A. Keough, G.A. Peterson, D.S. Ojima and D.S. Schimel -- Remediation of drinking water for rural populations / W.J. Hunter -- Remediation at the water treatment plant / L.D. McMullen -- Nitrogen management by producers : a multiple scale perspective / Pete J. Nowak, Laurence B. Cutforth, Perry E. Cabot and Bruce M. Kahn -- New policy directions / Andrew P. Manale.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Nitrogen fertilizers; Nitrogen fertilizers -- Environmental aspects; Electronic books